2018
DOI: 10.5194/isprs-archives-xlii-3-1103-2018
|View full text |Cite
|
Sign up to set email alerts
|

THE VEGETATION TRENDS AND DRIVERS IN BEIJING-TIANJING-HEIBEI REGION FROM 1982 TO 2013 BASED ON TIME SERIES GIMMS NDVI3g

Abstract: ABSTRACT:Vegetation plays a leading role in ecosystems. Plant communities are the main components of ecosystems. Green plants in ecosystems are the primary producers, and they provide the living organic matter for the survival of other organisms. The dynamics of most landscapes are driven by both natural processes and human activities. In this study, the growing season GIMMS NDVI3g and climatic data were used to analyse the vegetation trends and drivers in Beijing-Tianjin-Hebei region from 1982 to 2013. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The content of tree pollen was the highest throughout the core, and the pollen of deciduous trees (43.4%) dominated by Quercus and Betula was in the majority. The mixed coniferous and deciduous forest dominated by Quercus and Pinus formed the climax community in warm-temperate zones (Liu, 1996), which suggested that the climate was warm and wet and thus suitable for tree growth (Figures 4 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…The content of tree pollen was the highest throughout the core, and the pollen of deciduous trees (43.4%) dominated by Quercus and Betula was in the majority. The mixed coniferous and deciduous forest dominated by Quercus and Pinus formed the climax community in warm-temperate zones (Liu, 1996), which suggested that the climate was warm and wet and thus suitable for tree growth (Figures 4 and 6).…”
Section: Discussionmentioning
confidence: 99%